Photo-controlled liquid metal nanoparticle-enzyme for starvation/photothermal therapy of tumor by win-win cooperation. (October 2019) - Hu, Jing-Jing; Liu, Miao-Deng; Gao, Fan; Chen, Ying; Peng, Si-Yuan; Li, Zi-Hao; Cheng, Han; Zhang, Xian-Zheng
Abstract: Here, a highly cooperative liquid metal nanoparticle-enzyme (LM@GOX) was constructed for combinational starvation/photothermal therapy of tumor. It was found that the enzyme activity of glucose oxidase (GOX) could be strengthened along with the increased temperature within a given range and its optimal activity is around about 43–60 °C. Utilizing the photothermal conversion ability of liquid metal (LM), the GOX catalytic efficiency could be photo-controlled with improved starvation therapeutic efficiency. Furthermore, due to the accelerating blood flow during the photothermal therapy (PTT), the hypoxic situation in tumor tissues could also be relieved, which would contribute to conquering the hypoxia-suppressed GOX catalysis. In the meanwhile, the severe thermo-resistance of tumor cells during PTT process could be overcome by GOX induced decrease of adenosine triphosphate (ATP) and heat shock proteins (HSPs) level, eventually leading to an improved therapeutic effect of PTT. Both in vitro and in vivo studies proved that LM@GOX could significantly inhibit the growth of solid tumor under NIR illumination by a win-win cooperative starvation/photothermal therapy. Graphical abstract: Image 1